Quantitative Analysis of Coronary Vessels with Optimized Intracoronary CT Number - Komatsu, Sei (Public Library of Science, 2014)
BACKGROUND: Variability in intracoronary computed tomography (CT) number may influence vessel quantification. We confirmed the feasibility of a novel method for measuring vessel diameter and area using coronary CT angiography (CCTA) with an optimized intracoronary CT number, 350 HU. METHODS: We performed intravascular ultrasound (IVUS) imaging in 52 patients with significant stenosis detected by coronary CT angiography targeting 350 HU using a CT number-controlling system. We measured 0-to-0 HU distances in the cross-sectional coronary images of 32 patients. We analyzed the ratio of 0-to-0 HU distances in CT images to media-to-media distances in IVUS images (C:I ratio). The area of ≥0 HU for 103 representative points in the remaining 20 patients was compared to the area of the traced external elastic membrane (EEM) in IVUS images. RESULTS: There was a strong correlation between 0-to-0 HU distance in CT images and media-to-media diameter in IVUS images (r = 0.97, p<0.001). The C:I ratio was 1.1. EEM area was estimated by dividing the area of ≥0 HU by the square of C:I. There was also a strong correlation between the estimated EEM area and the EEM area in IVUS images (r = 0.95, p<0.001). CONCLUSIONS: Media-to-media diameter and EEM area can be estimated by CCTA targeting the optimized intracoronary CT number when blood vessel borders are defined at 0 HU.